1989
DOI: 10.1016/0014-5793(89)81690-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of four lipocortin proteins and phosphorylation of lipocortin I by protein kinase C in cytosols of porcine thyroid cell cultures

Abstract: Rewved 19 October I989Four proteins of the hpocortm family, hpocortm I (35 kDa), hpocortm II (36 kDa), lrpocortm V (32 kDa) and hpocortm VI (67-70 kDa), were ldentlfied m the cytosols of 2-day-old cultures of thyroid cells Only hpocortm I was phosphorylated m vitro m fully dlfferentlated, thyroid strmulatmg hormane-treated cells (0 1 mu/ml) Protem kmase C was the only kmase actlvlty which phosphorylated hpocortm I Phosphorylatlon shifted its pI from 6 9 to 6 6 The m v&o phosphorylatlon of hpocorCm I was tmpalr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Human ANXA1 (also called calpactin II, lipocortin 1, or p35) belongs to the annexin superfamily, which consists of at least 11 different, abundant, and ubiquitously expressed proteins (6). In vitro studies have suggested that ANXA1 may play an important role in the regulation of both insulin secretion (6 -12), including stimulation of insulin secretion by the arachidonic acid-phospholipase A 2 (cPLA 2 ) pathway (13,14) or in the signal cascades initiated from the insulin receptor (7,8).…”
mentioning
confidence: 99%
“…Human ANXA1 (also called calpactin II, lipocortin 1, or p35) belongs to the annexin superfamily, which consists of at least 11 different, abundant, and ubiquitously expressed proteins (6). In vitro studies have suggested that ANXA1 may play an important role in the regulation of both insulin secretion (6 -12), including stimulation of insulin secretion by the arachidonic acid-phospholipase A 2 (cPLA 2 ) pathway (13,14) or in the signal cascades initiated from the insulin receptor (7,8).…”
mentioning
confidence: 99%
“…Activation of PKC by growth factors, hormones or phorbol esters leads to the phosphorylation of many endogenous proteins which mediate the effects of these agonists on cellular processes such as proliferation and differentiation. Annexins are among these substrates phosphorylated by PKC (Khanna et al, 1986;Schlaepfer and Haigler, 1988;Antonicelli et al, 1989;Isacke et al, 1986;Could et al, 2986). In mesangial cells, we have shown that actiCrmespondence to J.-P. Oudinet PtdIns(4,5)P2, phosphatidylinositol 4,s-bisphosphate; Ins(l,4,5)P3, inositol 1,4,5-trisphosphate; acyl,Gro, diacylglycerol; PKC, protein kinase C; c-, conventional; n-, novel; a-, atypical.…”
mentioning
confidence: 99%
“…After permeabilization, the cell membrane was clearly stained (Fig. 1B) [31], cultured rat renomedullary interstitial cells [4], porcine thyroid cells [32], human endothelial cells [33] and human mononuclear cells [34]. Several reports have shown that the 35 kDa and 67-70 kDa lipocortin-like protein are closely related with respect to sequence, antiserum cross-reactivity and binding of Ca 2+ and phospholipid (see [35] for refs).…”
Section: Resultsmentioning
confidence: 99%
“…Lipocortin I is a substrate for both the EGF receptor tyrosyl kinase [36] and the protein kinase C (PKC) [2,37]. Antonicelli et al [32] recently showed that among four proteins (32, 35, 36 and 67-70 kDa) of the lipocortin family, only lipocortin I was the endogenous substrate for the PKC in thyroid-stimulating hormone (TSH) treated cells. This is the first evidence that lipocortin-like proteins can be produced and released by human airway submucosal secretory cells.…”
Section: Resultsmentioning
confidence: 99%